Release of CO2 into the atmosphere by rhizosphere activity of different crops in the coffee-growing region of the department of Cauca - Quintín L., Carlos; Montoya S., Juan Carlos; Paz N., Iván Enrique (Revista de Ciencias Agrícolas, 2015)
Quantifying crop-derived CO2 emissions allows an accurate insight into the contribution of agriculture to these emissions. This research sought to establish the amount of CO2 emissions and microbial biomass behavior in crop managements of coffee Coffea arabica L., cassava M. esculenta, beans P. vulgaris, and lettuce L. sativa, in order to determine which crop caused the highest CO2 emissions depending on management type, technified or traditional. CO2 field emissions were measured according to the method proposed, biomass was measured using an estimation method (microbial biomass), based on microbial carbon, and a method of fumigation-extraction. Coffee showed the highest CO2 emissions. Crop management type did not affect CO2 emissions. Furthermore, climate conditions affected respiration rates among crops, indicating that coffee had higher respiration rates during rainy periods compared to the other crops.